1999
DOI: 10.1034/j.1600-051x.1999.260605.x
|View full text |Cite
|
Sign up to set email alerts
|

The gingival plasma cell infiltrate in HIV‐positive patients with periodontitis is disorganized

Abstract: Patients infected with the human immunodeficiency virus (HIV) are highly susceptible to chronic marginal periodontitis (CMP) and the lesion is generally characterized by abundant plasma cell infiltration. HIV-induced reduction of CD4+ T cells may indirectly affect local production of immunoglobulins (Ig). Gingival biopsies taken from 10 HIV+ and 12 HIV- control patients with CMP were washed, fixed in ethanol and embedded in paraffin. Sections were examined after immunohistochemical staining with monoclonal ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0
5

Year Published

2000
2000
2014
2014

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 36 publications
2
12
0
5
Order By: Relevance
“…FcaRI-bearing neutrophils were predominantly located adjacent to the deeper part of the periodontal pocket where large numbers of microorganisms reside. This indicates that FcaRI-mediated phagocytosis of IgA-opsonized antigens is likely to aid in elimination of penetrating bacteria, because (1) about 10%-30% of the plasma cells in periodontal lesions produce IgA (Okada et al 1983, Takahashi et al 1997, Myint et al 1999), (2) IgA antibodies specific for potential periodontal pathogens are found in serum and gingival fluid from patients with CMP (Tolo & Schenck 1985, Condorelli et al 1998, Landry 1995, and (3) we observed considerable numbers of subgingival plaque bacteria coated with IgA (present study). FcaRI on neutrophils has a higher affinity for IgA than FcgRs on the same cells have for IgG, and IgA-mediated phagocytosis in the tissue may therefore be more effective than that mediated by IgG (Mazengera & Kerr 1990, Stewart et al 1994, Raghavan & Bjorkman 1996.…”
Section: Discussionsupporting
confidence: 55%
“…FcaRI-bearing neutrophils were predominantly located adjacent to the deeper part of the periodontal pocket where large numbers of microorganisms reside. This indicates that FcaRI-mediated phagocytosis of IgA-opsonized antigens is likely to aid in elimination of penetrating bacteria, because (1) about 10%-30% of the plasma cells in periodontal lesions produce IgA (Okada et al 1983, Takahashi et al 1997, Myint et al 1999), (2) IgA antibodies specific for potential periodontal pathogens are found in serum and gingival fluid from patients with CMP (Tolo & Schenck 1985, Condorelli et al 1998, Landry 1995, and (3) we observed considerable numbers of subgingival plaque bacteria coated with IgA (present study). FcaRI on neutrophils has a higher affinity for IgA than FcgRs on the same cells have for IgG, and IgA-mediated phagocytosis in the tissue may therefore be more effective than that mediated by IgG (Mazengera & Kerr 1990, Stewart et al 1994, Raghavan & Bjorkman 1996.…”
Section: Discussionsupporting
confidence: 55%
“…Reduced numbers of Langerhans 40 and remarkably increased numbers of plasma cells 41 have been demonstrated in the gingival tissue of HIV-infected patients with periodontitis. It is conceivable that different immunodeficiencies may be present in HIV-infected patients.…”
Section: Discussionmentioning
confidence: 98%
“…The interactions between antiretroviral drugs and periodontal diseases have not yet been elucidated, but clinically, there seems to be more relevant constitution than general immune reconstitution under HAART that normalizes immune response in the HIV‐infected patient. In the oral cavity, the mechanisms of HIV‐related immune suppression were described as follows: (a) a limited chemotaxis of neutrophilic granulocytes in the initial phase of periodontal disease defense; (b) a dysfunction of macrophages with CD4 surface markers in the succeeding phase of phagocyte activity; and (c) a disorganization of gingival B‐ and T‐lymphocyte activity and their humoral products, such as immune globulins . Based on this, all stages of the host‐dependent immunological defense against periodontal disease are compromised by HIV infection.…”
Section: Discussionmentioning
confidence: 99%